Taxonomy of the genus Autosticha Meyrick (Lepidoptera: Autostichidae) in China: Descriptions of fifteen new species - Tao, Zhulin; Wang, Yuqi; Wang, Shuxia (Zootaxa, 2021)
Fifteen new species of the genus Autosticha Meyrick are described from China: A. annulata sp. nov., A. flabellata sp. nov., A. rhombea sp. nov., A. auriculata sp. nov., A. apicilata sp. nov., A. bomiensis sp. nov., A. longispina sp. nov., A. angustivalva sp. nov., A. basiprocessa sp. nov., A. semicircularia sp. nov., A. trapeziformis sp. nov., A. turriformis sp. nov., A. ventericoncava sp. nov., A. furcillata sp. nov. and A. ornithorhyncha sp. nov. Images of adults and genitalia are provided.